Las elecciones y la izquierda democrática en Medellín, 1970-1990 (2011)
ABSTRACT: This article shows a short part of the reality local politic between 1970 and 1990, when the politic regime open the doors of the electoral participation to several politic movements. This permits that organizations how the Communist Colombian Party, the Workers Independent Revolutionary Movement and the Patriotic Union were part of electoral scene. So, this lines offers a view of the alliances that the democratic left made during 20 years in Medellin with others parties y different sectors of the oppositions, and how that constructed some organizations before the elections with the objective of obtain more power.